Exact conservation of quantum numbers B, S and Q in the statistical description of high energy collisions - Marais, Mark (Department of Physics, 2016)
High energy collisions are studied assuming that particles can be described by a hadron gas in thermal and chemical equilibrium. The exact conservation of baryon number, strangeness and charge are explicitly taken into account. For heavy ions the effect arising from the neutron surplus becomes important and leads to a substantial increase in e.g. the π-/π+ ratio. Special emphasis is therefore put on the exact conservation of charge. Comparison with experimental results from the E866 collaboration at BNL is made.